miR-214-mediated downregulation of RNF8 induces chromosomal instability in ovarian cancer cells - Wang, Zheng (Cell Cycle, 2014)
Defective DNA damage response (DDR) is frequently associated with carcinogenesis. Abrogation of DDR leads to chromosomal instability, a most common characteristic of tumors. However, the molecular mechanisms underlying regulation of DDR are still elusive. The ubiquitin ligase RNF8 mediates the ubiquitination of γH2AX and recruits 53BP1 and BRCA1 to DNA damage sites which promotes DDR and inhibits chromosomal instability. Though RNF8 is a key player involved in DDR, regulation of its expression is still poorly understood. Here, we show that miR-214 could abrogate DDR by repressing RNF8 expression through direct binding to 3′-untranslated region (3′ UTR) of RNF8 mRNA in human ovarian cancer cells. Antagonizing miR-214 by expressing its inhibitors in A2780 cells significantly increased RNF8 expression and thus promoted DNA damage repair. Consistent with the role of miR-214 in regulating RNF8 expression, the impaired DNA repair induced by miR-214 overexpression can be rescued by overexpressing RNF8 mRNA lacking the 3′ UTR. Together, our results indicate that down-regulation of RNF8 mediated by miR-214 impedes DNA damage response to induce chromosomal instability in ovarian cancers, which may facilitate the understanding of mechanisms underlying chromosomal instability.